2012
DOI: 10.1111/j.1468-3083.2012.04690.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of adding the psychotropic drug escitalopram in the treatment of patients suffering from moderate–severe psoriasis and psychiatric comorbidity: a retrospective study

Abstract: Our study suggests that psychological interventions and antidepressant medications may improve perceived symptom severity, quality of life and major compliance to the treatment in selected patients (suffering from psoriasis and mood disturbance), without a clinician necessarily being able to see an impact on psoriasis severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…In a retrospective study, escitalopram reduced depressive and physical symptoms 78% in 38 patients with moderate-to-severe psoriasis compared to a 22% reduction with placebo as measured by the Hamilton Rating Scale for Depression. Furthermore, there was a statistically significant reduction in pruritus with escitalopram (35%) versus the control group (11% increase) [21].…”
Section: Impact Of Treating Depression In Psoriasis Patientsmentioning
confidence: 85%
“…In a retrospective study, escitalopram reduced depressive and physical symptoms 78% in 38 patients with moderate-to-severe psoriasis compared to a 22% reduction with placebo as measured by the Hamilton Rating Scale for Depression. Furthermore, there was a statistically significant reduction in pruritus with escitalopram (35%) versus the control group (11% increase) [21].…”
Section: Impact Of Treating Depression In Psoriasis Patientsmentioning
confidence: 85%
“…It is possible to resort to the use of drug treatments such as anxiolytics and/or selective serotonin reuptake inhibitors (SSRI). Several studies have reported the improvement in skin symptoms following the initiation of SSRI treatment . Nonpharmacological treatments have been associated, such as relaxation, a method teaching how to reduce muscle tone, and meditation .…”
Section: Stress Management During Psoriasismentioning
confidence: 99%
“…Several studies have reported the improvement in skin symptoms following the initiation of SSRI treatment. 107,109 Nonpharmacological treatments have been associated, such as relaxation, a method teaching how to reduce muscle tone, 110,111 and meditation. 112 Meditation is reported to reduce by 30-35% the predefined time required to obtain a clinical response to PUVA therapy or UVB phototherapy.…”
Section: Stress Management During Psoriasismentioning
confidence: 99%
“…In psoriasis patients, psychological interventions and antidepressant medications have been shown to improve the patient's perception of symptom severity, compliance with treatment, and overall quality of life independent of any changes in clinical severity [13] . Therefore, patients with psychophysiologic disorders may benefit from a holistic approach that addresses both the dermatologic condition as well as the psychological status.…”
Section: Psychophysiologic Disordersmentioning
confidence: 99%